Airway-centered invasive pulmonary aspergillosis featuring histopathologic fruiting bodies in an immunocompetent patient with a rare incidental finding of thyroid gland Schwannoma: a case report - Imad Majeed; Sundal Aziz; Zaraq Rashid khan; Forest Arnold (BMC Infectious Diseases)
Abstract Introduction Invasive pulmonary aspergillosis (IPA) is typically associated with immunocompromised patients, but rare occurrences have been documented in immunocompetent individuals. This presents diagnostic and therapeutic challenges due to atypical presentations and less apparent risk factors. Case presentation A 67-year-old Cambodian American female with a history of stable pulmonary nodules and a left neck schwannoma presented with a two-week history of cough and hemoptysis. Imaging revealed a left lower lobe lung mass suspicious for malignancy. Biopsy and bronchoalveolar lavage confirmed the diagnosis of invasive pulmonary aspergillosis, despite the patient’s lack of traditional immunosuppressive risk factors. Her environmental exposures, including a recent trip to Cambodia and a history of gardening, were likely contributing factors. The diagnosis of IPA in this immunocompetent patient was established through a combination of clinical presentation, radiographic findings, and microbiological evidence. Bronchoalveolar lavage and galactomannan testing were crucial in identifying the presence of Aspergillus. Histopathological examination of the biopsy specimen revealed the presence of Aspergillus fruiting bodies, an uncommon finding indicative of invasive disease. The patient was promptly started on voriconazole, the first-line antifungal agent for IPA, which led to an improvement in her symptoms. Moreover, her left neck mass schwannoma in the thyroid bed was also a rare entity. Conclusion This case highlights the importance of considering IPA as a differential diagnosis in immunocompetent individuals with relevant environmental exposures and preexisting lung conditions, even in the absence of classic immunosuppressive risk factors.